Effect of gelling temperature and calcium chloride concentration on rheological and microstructural properties of acid‐induced gels of milk protein concentrates. Issue 10 (23rd September 2018) - Wang, Hong; Wang, Yunna; Yuan, Dongdong; Cao, Jialu; Chen, Liankun; Li, Yan; Zhang, Liebing
Abstract : Milk protein concentrates (MPCs) serve as novel functional ingredients in the food industry and, in addition, are highly nutritional. The aim of this study is to evaluate the effects of two different concentration methods, namely nanofiltration and evaporation, on MPC gel properties. In this research, the MPC gels were produced using glucono‐ δ ‐lactone (GDL) as the acidifier, at different temperatures (25, 30, 35, 40, and 45 °C) and CaCl2 (between 5 and 30 mmol/L). The dependence properties of the MPC gels were observed, including storage modulus (G′), loss tangent (tan δ ), firmness and microstructure. Measured at the same level of temperature and CaCl2, EP‐MPC produced higher firmness and G′ value compared to NF‐MPC. Also, EP‐MPC exhibited a more homogeneous, branched microstructure of gel network than NF‐MPC. These results indicated that EP‐MPC has superior gel properties compared to NF‐MPC, which contribute comprehensive information to improve decisions regarding concentrations in the production of MPC gels. Practical applications: This study investigated the effects of concentration methods (nanofiltration and evaporation) and pretreatment parameters (gelation temperature and CaCl2 concentrations) on the gel properties of MPCs in terms of rheological behavior and texture characteristics. The results have manifested that the differences between the two kinds of MPCs produced from evaporation and nanofiltration depend on the levels of gelation temperature and CaCl2 concentrations, giving opportunity for the different MPCs to achieve similar gel properties. Manufacturers could benefit from this research in reasonably deciding concentration way in the production of MPC gels for different applications.